Analisis Reaksi Pasar Atas Peristiwa Pilkada Serentak Tahun 2018 - Wahyu Suryani, Ni Nyoman; Rasmini, Ni Ketut (E-Jurnal Akuntansi, 2019)
This study aims to determine market reaction in the event of simultaneous regional elections in 2018. This research is an event study with a period of observation for 7 days. The study was conducted on companies classified as LQ45 from February to July 2018. The population in this study was 45 companies. The method of determining the sample used is a non probability sampling method with a purposive sampling technique. The sample obtained was 37 companies. The market reaction to the 2018 simultaneous regional elections was measured using abnormal return and trading volume activity. The data analysis technique used is paired-sample t-test. The test results show that there is no difference in average abnormal return and trading volume activity before and after the events of simultaneous regional elections. This shows that simultaneous regional elections in 2018 did not cause market reaction because there was no information content on the event. Keywords:  Event study, abnormal return, politics